Implementasi Model Discovery Learning dalam Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti di SMAN 1 Bulukumba - Muhammad Asbar, Andi (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
The results of research on the implementation of discovery learning model on the subjects of Islamic Education and Character in SMAN 1 Bulukumba, is a model of discovery learning has been applied by Islamic Education Teachers and Character in SMAN 1 Bulukumba in terms of input, process and output components. In the learning needs to be evaluated, especially on aspects of process components and output components on aspects of student skills. Educators are required to maximize in applying the learning model in order to obtain a quality learning situation, active and develop the attitude and knowledge of students. The application of the discovery learning model is not an easy task, by which the teacher takes a lot of time and not all students are able to make the discovery, this model does not apply to all topics. Related to the time and strategy of discovery learning requires a longer duration, due to the rational thinking ability of students is still limited and cultural factors or habits that still use the old learning patterns. The implication of this research, it is expected that the teacher of Islamic Education and Character can implement the scientific approach of discovery learning model in the learning process in class well, evaluate, repair and development both in terms of planning, implementation and assessment in using discovery learning model to run effective and systematic. And the creation of student-centered learning oriented development of attitudes, knowledge and skills of students.